Increases in Retrograde Injury Signaling Complex-Related Transcripts in Central Axons following Injury - Gunja K. Pathak; Hannah Ornstein; Helim Aranda-Espinoza; Amy J. Karlsson; Sameer B. Shah (Neural Plasticity)
Axons in the peripheral nervous system respond to injury by activating retrograde injury signaling (RIS) pathways, which promote local axonal protein synthesis (LPS) and neuronal regeneration. RIS is also initiated following injury of neurons in the central nervous system (CNS). However, regulation of the localization of axonal mRNA required for LPS is not well understood. We used a hippocampal explant system to probe the regulation of axonal levels of RIS-associated transcripts following axonal injury. Axonal levels of importin β1 and RanBP1 were elevated biphasically at 1 and 24 hrs after axotomy. Transcript levels for β-actin, a prototypic axonally synthesized protein, were similarly elevated. Our data suggest differential regulation of axonal transcripts. At 1 hr after injury, deployment of actinomycin revealed that RanBP1, but not importin β1, requires de novo mRNA synthesis. At 24 hrs after injury, use of importazole revealed that the second wave of increased axonal mRNA levels required importin β-mediated nuclear import. We also observed increased importin β1 axonal protein levels at 1 and 6 hrs after injury. RanBP1 levels and vimentin levels fluctuated but were unchanged at 3 and 6 hrs after injury. This study revealed temporally complex regulation of axonal transcript levels, and it has implications for understanding neuronal response to injury in the CNS.